Interindividual variation in carcinogen metabolism and bladder cancer risk. - Vineis, P (1992)
Epidemiological studies indicate that subjects of the genetically based slow acetylator phenotype may be at higher risk for bladder cancer than fast acetylators, particularly when they are exposed to carcinogenic arylamines: N-acetylation is a detoxification step in the metabolism of some arylamines. We describe two collaborative studies on tobacco smoking, in which markers of internal dose (arylamine-hemoglobin adducts) and markers of genetically-based metabolic polymorphism have been coupled. In the first investigation, we found that hemoglobin adducts formed by mononuclear arylamines have high reciprocal correlation coefficients, as do adducts from binuclear arylamines. This tendency of adducts with structurally similar arylamines to correlate reciprocally explains a large proportion of the residual variance seen after controlling for smoking habits (number and type of cigarettes). In the second study, the concentration of 4-amino-biphenyl-hemoglobin adducts varied according to three independent determinants: number of cigarettes, type of tobacco (air or flue cured), and acetylator phenotype (slow and fast). The dose-response relationship between the amount of tobacco smoked and level of 4-aminobiphenyl-hemoglobin adducts in the slow acetylators (with an immediate steep increase of the adducts) was different from that in the fast acetylators (with a more regular increase). These findings from "molecular epidemiology" may contribute to an understanding of the role of metabolic polymorphism in human carcinogenesis.